Service creativity, service excellence, and digital marketing on repeat purchase behavior mediated by customer satisfaction: Educational insights from wellness yoga programs - Ramdhani, Rommy Mochamad; Usman, Bahtiar; Yaputra, Hermanto; Rosadi , Barkah (ARKA INSTITUTE, 2024)
This study explores the influence of service creativity, service excellence, and digital marketing on repeat purchase behavior, with a focus on the educational aspects of wellness yoga programs. Conducted across various regions including Bandung, Klaten, Mojokerto, and Ubud, with a sample of 200 respondents, the research employed AMOS 24 for data analysis. The findings reveal that service excellence, digital marketing strategies, customer satisfaction, and brand image significantly affect repeat purchase behavior. Notably, brand image has a strong influence, potentially fostering customer loyalty and repeat purchases. The study highlights the importance of understanding the educational needs of yoga practitioners, suggesting that yoga studio managers should directly engage with practitioners to tailor services to their specific learning needs. This research contributes to the educational field by offering insights into how service-dominant logic can enhance the learning experience within wellness yoga programs. It underscores the necessity for yoga programs to prioritize service quality, thereby enhancing the educational value and overall effectiveness of yoga health tourism.